(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article discusses Islamic finance, a system that emerged in the global financial landscape nearly 14 centuries ago but is only now being introduced into the financial market of Uzbekistan. Islamic finance differs from the conventional financial system due to its emphasis on fairness, adherence to “halal” principles, and equitable risk-sharing. The article examines the challenges, shortcomings, and ongoing efforts related to the implementation of this system in Uzbekistan’s financial sector.